PEMANFAATAN APLIKASI QUIZIZZ SEBAGAI INOVASI MEDIA PEMBELAJARAN DI MASA PANDEMI COVID-19 BAGI GURU SD NEGERI 101877 TANJUNG MORAWA - Syibrina Jihan Lubis; Dinda Widyastika; Rudi Hermansyah Sitorus (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
The purpose of this study was to determine the use of the Quizizz application in learning during the Covid-19 pandemic for teachers at SD Negeri 101877 Tanjung Morawa. This type of research uses a descriptive qualitative approach. This research was conducted at SDN 101877 Tanjung Morawa. The research subjects were teachers and students of grade V SD Negeri 101877 Tanjung Morawa. Data collection techniques in this study were obtained from the results of observations, interviews, documentation and filling out questionnaires by students. The results of online learning research using the Quizizz application are that learning becomes fun, increases focus in learning, is more enthusiastic, and stimulates students to understand questions better and makes it easier for teachers to analyze students' questions and answers.